Effects of oxidant and dopant loadings on direct ultrasonic irradiated polyaniline with nanostructure - Zheng, Xuefeng (2020)
Polyaniline (PANI) has been applied in many fields nowadays. In this study, di-rect ultrasonic irradiation, which means immersing the ultrasonic horn directly into the reaction solution, was used to polymerize polyaniline at frequency of 20 kHz, power of 600W. The overall objective of this study was to synthesize PANI with nanostructure and high conductivity under direct ultrasonic irradiation. The effects of oxidant, viz., ammonium persulfate (APS) and dopant, viz., hydrochloric acid (HCl) concentration on the structure integrity, morphology, and electrical conductivity properties of the pre-pared polyaniline were examined. As the molar ratio of APS to aniline varied from 0.1 to 1.25, the conductivity of PANI samples reached a maximum of 0.24 S/cm at the ratio of 1. Characteristic peaks at 1558, 1477, 1296, and 1226 cm-1 corresponded to quinonoid ring stretching, benzenoid ring (B) stretching, C-N stretching of secondary aromatic amine, and C-N stretching in B-NH-B-NH-B unit showed in the Fourier transform in-frared (FTIR) spectra, respectively. In the ultra violet-visible (UV-vis) spectra, the in-tensity ratio of absorbance bands at 570-670 nm and 330-400, denoted as p-p* excitation of quinonoid segment and p-p* excitation of benzenoid part respectively, attained a zen-ith at APS/aniline molar ratio of 1. The area percentage of three sharp, equal intensity, equal distant peaks at 7.02, 7.14, 7.27 assigned to ammonium protons reached a maxi-mum at APS/aniline molar ratio of 1 in the nuclear magnetic resonance (NMR) spec-troscopy. As the molar ratio of APS/aniline increased, four peaks at 2?=8.7°, 14.8°, 19.9° and 25.2° appeared in the X-ray diffraction (XRD) spectroscopy, and the crystallinity achieved a maximum at the molar ratio of 1. Field emission scanning electron micros-copy (FESEM) and high-resolution transmission electron microscopy (HRTEM) images showed vein-like structure, nanorods, nanofiber, bridge like structure and plate when APS/aniline molar ratio increased. Subsequently, the concentration of HCl was changed from 0.01 M to 2 M under the same preparation method with the optimized molar ratio of APS/aniline of 1. The conductivity of PANI samples increased with the increase of HCl concentration and reached a maximum of 0.5 S/cm at HCl concentration of 2 M. Characteristic peaks at 1554, 1480, 1287, and 1246 cm-1 corresponded to quinonoid ring stretching, benzenoid ring (B) stretching, C-N stretching of secondary aromatic amine, and C-N stretching in B-NH-B-NH-B unit showed in the FTIR spectra, respectively. In the UV-vis spectra, the intensity ratio of absorbance bands at 590-620 nm and 330-360, denoted as p-p* excitation of quinonoid segment and p-p* excitation of benzenoid part respectively, attained a zenith at HCl concentration of 2 M. The area percentage of three sharp, equal intensity, equal distant peaks at 7, 7.13, 7.26 assigned to ammonium protons reached a maximum at HCl concentration of 2 M in the NMR spectroscopy. As the HCl concentration increased, four peaks at 2?=8.6°, 14.9°, 19.9° and 25.2° appeared in the XRD spectroscopy, and the crystallinity achieved a maximum at the concentration of 2 M. FESEM images showed nanorods, nanostick, and petal-like structures when HCl concentration increased.